Ibn Khaldun and John Locke’s Thoughts, Reframing Contemporary Education World Order - Qasserras, Mohammed (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
Exploring two international philosophers’ scholarship with lasting effect on education theory through a comparative qualitative study would help to synthesize alternative tools and epistemology to address contemporary education landscape and human-to-human interaction. Ibn Khaldun’s and John Locke’s intellectual legacy brought revolutionary knowledge based on their empirical observation (Assabiyya & Social Contract) which has inspired various social, political as well as modern education concepts. Indeed, though Ibn Khaldun and John Locke belong to dissimilar schools of thought, they share a number of philosophical and educational ideas deemed to offer new remedies to our current education and cross-cultural interactions by transforming the learner at the center of a new learning world order.